Study on fibre reinforced concrete using manufactured sand as fine aggregate and domestic waste plastics as fibres - Kandasamy, R.; Murugesan, R. (Journal of Structural Engineering, 2024)
Manufactured sand/ Crushed stone sand is defined in IS 383 as “Fine aggregate produced by crushing hard stone”. This means that it is a controlled crusher dust which does not have more than 20% passing 150 micron sieve and not more than 15% passing 75 micron sieve. Normally, the crusher dust is thrown away as a waste material and river sand is used in concrete at a price. By using the crusher dust as crushed stone sand/ manufactured sand, one can avoid buying river sand for concrete and pay for only transporting the crushed stone sand like the coarse aggregates. Hence, it is prudent to conserve natural river sand for other utilities than for concrete. The domestic plastics waste is causing a lot of harm to environment and hence their disposal has become a prime concern. The use of plastic wastes in concrete has not been well documented. Hence, investigations were carried out on fibre reinforced concrete with manufactured sand as fine aggregate and domestic waste plastics as fibres. A detailed investigation has been carried out on three types of concrete namely, ordinary concrete with river sand, concrete using manufactured sand as complete replacement for sand and fibre reinforced concrete with manufactured sand and domestic waste plastics as fibres. The mechanical characteristics, viz., compressive strength, split tensile strength and flexural strength were evaluated.